101k views
0 votes
Which of the following expressions is 7a-4 (2a-4) In simplest form

User Babatunde
by
5.0k points

1 Answer

5 votes

Given

we are given an expression


7a-4(2a-4)

Required

we need to write the above expression in simplest form.

Step-by-step explanation

We know that


a*(b-c)=a* b-a* c

Now the given expression is


\begin{gathered} 7a-4(2a-4)=7a-4*(2a-4)=7a-(4*2a)-(4*(-4)) \\ =7a-8a-(-16)=-a+16\text{ } \\ \text{ } \end{gathered}

So option a is correct.

User Imtiaz Pabel
by
4.8k points